1984
DOI: 10.1038/308467a0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the leukaemogenicity of a murine retrovirus by sequences within the long terminal repeat

Abstract: Although the murine retrovirus SL3-3 is highly leukaemogenic, in both the structure of its genome and in its properties of replication in tissue culture it closely resembles the nonleukaemogenic retrovirus Akv (refs 3, 4). An earlier investigation of the properties of recombinant SL3-3-Akv viruses localized the major determinant of leukaemogenicity outside the env gene, in a region of the viral genome that includes the gag gene and the noncoding long terminal repeat (LTR). To localize the determinant of SL3-3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
244
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(254 citation statements)
references
References 54 publications
8
244
1
Order By: Relevance
“…Enhancers have been identified in the U3 region of the long terminal repeats (LTRs) of retroviruses (17,19,20). More recently, the LTRs of murine leukemia viruses (MLVs) have been implicated in the specific type of neoplasia caused by these viruses (5,9,22,28), and it is possible that the sequences resembling enhancers are responsible for this specificity (4).…”
mentioning
confidence: 99%
“…Enhancers have been identified in the U3 region of the long terminal repeats (LTRs) of retroviruses (17,19,20). More recently, the LTRs of murine leukemia viruses (MLVs) have been implicated in the specific type of neoplasia caused by these viruses (5,9,22,28), and it is possible that the sequences resembling enhancers are responsible for this specificity (4).…”
mentioning
confidence: 99%
“…In a previous study, we demonstrated that Mlvi-2, a second common domain for provirus integration in MoMuLV-induced rat thymic lymphomas, also maps to mouse chromosome 15 (36). However, in contrast to Mlvi-1, Mlvi-2 could not be detected in hybrid HM25, suggesting that Mlvi-2 maps to the centromeric end of chromosome 15. Thus, the separation of Mlvi-J and Mlvi-2 in a hybrid apparently carrying a chromosome 15 The genetic mapping of Mlvi-J to chromosome 15 raised the possibility that this region of integration could contain the cellular oncogenes c-myc or c-sis.…”
Section: S Ppepementioning
confidence: 88%
“…2). These enzymes generated Mlvi-) specific fragments of 20 kb (KpnI) and 10 DNA contained mouse c-myc sequences, indicating that this hybrid line contains at least a fragment of the distal end of chromosome 15 (13). Thus, it can be concluded that the murine Mlvi-J homolog is present on chromosome 15 and probably maps to the distal end of this chromosome.…”
mentioning
confidence: 95%
See 2 more Smart Citations